FORMULASI EMULSI GANDA VIRGIN COCONUT OIL (VCO) DENGAN EMULGATOR SPAN 80 DAN TWEEN 60 - Yandi Syukri; Siti Zahliyatu; Maulia Ulfa (Universitas Islam Indonesia, 2008)
ABSTRACTVirgin Cocunut Oil (VCO) is a pure coconut oil, it has many advantages in health. It hasbeen circulated in market with unpleasant taste. Therefor, an innovation to find an acceptableformula by consumer should be carried out. The aimed of this research is to find out theinfluence of mix emulsifier toward physical stability of emulsion. Multiple emulsions w/o/wwere made by mix Span 80 with variation concentration 20%, 15%, 10%, and Tween 80. In orderto know the physical stability of emulsion w/o/w should be carried out viscosity test, separation inroom temperature, separation at 40ºC, separation due to centrifugation, creaming volume,paticle size, homogenity for 4 weeks storage, and respondent survey with 20 person. The testresult for 3 formulation emulsion for 4 weeks storage showed that formulation are nothomogeneous, but arter the formulas were shaken, it become homogeneous. In variousconcentration of Span 80, the longer preperations were storage the higher volume sedimentationand viscosity. Moreover, the longer preparations were storage, creaming volume and particle sizedecrease. Emulsifier combination between Span 80 with variation concentration 20%, 15%, 10%,and tween 60 in multiple emulsion w/o/w influenced physical stability multiple emulsi w/o/w.Moreover, this formulation also would be pleasant by consumen.Keywords: Multiple emulsion w/o/w, Span 80, Tween 60, Virgin Coconut Oil